Expression and Clinical Significance of Livin Protein in Hepatocellular Carcinoma. Issue 5 (3rd October 2013) - Guo, Hua; Gao, Ying-tang; Zhang, Qin; Jing, Li; Liu, Tong; Shi, Wen-xia; Zhai, Dao-kuan; Jing, Xiang; Du, Zhi
Abstract : In this study, the two-step PV method of immunohistochemistry was used to determine livin protein expression in HCC tissues, pericarcinoma tissues, hepatitis/hepatic cirrhosis tissues, and normal hepatic tissues, and livin protein expression was detected in the blood plasma of patients with HCC before and after surgery, subjects with hepatic cirrhosis and hepatitis, and healthy blood donors using ELISA. Livin protein expression was significantly higher in HCC tissues than that in normal hepatic tissues and hepatitis/hepatic cirrhosis tissues, with no significant difference between HCC tissues and pericarcinoma tissues. The HCC patients with positive livin protein expression had a significantly higher survival rate than those with negative livin protein expression. Livin protein expression was significantly higher in the blood plasma of patients with HCC before and after surgery and in patients with hepatic cirrhosis and hepatitis than that in healthy blood donors, whereas livin protein expression in the blood plasma of patients with HCC was not significantly different from that of patients with hepatic cirrhosis and hepatitis. Livin protein expression in HCC tissues did not correlate with that in the blood plasma of the same HCC patients. Livin protein expression may be a potential, effective indicator for assessing prognosis in patients with HCC.